Antibacterial and Osteoinductive Implant Surface Using Layer-by-Layer Assembly. (September 2021) - Hasani-Sadrabadi, M.M.; Pouraghaei, S.; Zahedi, E.; Sarrion, P.; Ishijima, M.; Dashtimoghadam, E.; Jahedmanesh, N.; Ansari, S.; Ogawa, T.; Moshaverinia, A.
Osseointegration of dental, craniofacial, and orthopedic implants is critical for their long-term success. Multifunctional surface treatment of implants was found to significantly improve cell adhesion and induce osteogenic differentiation of dental-derived stem cells in vitro. Moreover, local and sustained release of antibiotics via nanolayers from the surface of implants can present unparalleled therapeutic benefits in implant dentistry. Here, we present a layer-by-layer surface treatment of titanium implants capable of incorporating BMP-2–mimicking short peptides and gentamicin to improve their osseointegration and antibacterial features. Additionally, instead of conventional surface treatments, we employed polydopamine coating before layer-by-layer assembly to initiate the formation of the nanolayers on rough titanium surfaces. Cytocompatibility analysis demonstrated that modifying the titanium implant surface with layer-by-layer assembly did not have adverse effects on cellular viability. The implemented nanoscale coating provided sustained release of osteoinductive peptides with an antibacterial drug. The surface-functionalized implants showed successful osteogenic differentiation of periodontal ligament stem cells and antimicrobial activity in vitro and increased osseointegration in a rodent animal model 4 wk postsurgery as compared with untreated implants. Altogether, our in vitro and in vivo studies suggest that this approach can be extended to other dental and orthopedic implants since this surface functionalization showed improved osseointegration and an enhanced success rate.